'Children in a Ragged State': Seeking a Biocultural Narrative of a Workhouse Childhood in Ireland during the Great Famine (1845–1852). (2nd July 2016) - Geber, Jonny
Abstract : Despite the fact that more than half of all who died in the Great Famine in Ireland from 1845 to 1852 were children, relatively little research has focused on their experiences of this period. Following the archaeological excavation of a Famine-period workhouse mass burial ground in Kilkenny City, the physical reality of the catastrophe for over 500 of its child victims has become evident. The experience of poverty, famine and institutionalization can be discerned from markers of stress in their skeletons and, when discussed in a biocultural research setting, these markers provide a unique insight into the tragic veracity of one of the worst subsistence crises in history. The historical records reveal that amongst high child mortality rates, the well-being of the children was in fact a priority for workhouse officials. Though many died, a large number of children's lives would also have been saved in the institution.